2011
DOI: 10.1016/j.wocn.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Natural Referent Vowel (NRV) framework: An emerging view of early phonetic development

Abstract: The goal of this paper is to provide an overview of an emerging new framework for understanding early phonetic development -The Natural Referent Vowel (NRV) framework. The initial support for this framework was the finding that directional asymmetries occur often in infant vowel discrimination. The asymmetries point to an underlying perceptual bias favoring vowels that fall closer to the periphery of the F1/F2 vowel space. In Polka & Bohn (2003) we reviewed the data on asymmetries in infant vowel perception an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
217
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(239 citation statements)
references
References 60 publications
17
217
2
3
Order By: Relevance
“…Polka and Bohn (2003) initially proposed that this early vowel bias plays an important role in the development of vowel perception by establishing stable referents that help young infants attend to and differentiate vowels during the period when they are learning phonetic categories. Broadly consistent with this idea, more recent studies have shown that linguistic experience fine-tunes this initial vowel bias to optimize access to native-language vowel categories during speech processing (Polka & Werker, 1994;Polka & Bohn, 2011;Pons, Albareda-Castellot, Sebastián-Gallés, 2012;Dufour, Brunelliere, & Nguyen, 2013;Tyler, Best, Faber & Levitt, 2014). For example, with respect to German /u-/y/, monolingual English-speaking adults continue to show the same asymmetry as English-and German-learning infants, while German-speaking adults show symmetric (and near perfect) discrimination of this contrast (Polka & Bohn, 2011).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Polka and Bohn (2003) initially proposed that this early vowel bias plays an important role in the development of vowel perception by establishing stable referents that help young infants attend to and differentiate vowels during the period when they are learning phonetic categories. Broadly consistent with this idea, more recent studies have shown that linguistic experience fine-tunes this initial vowel bias to optimize access to native-language vowel categories during speech processing (Polka & Werker, 1994;Polka & Bohn, 2011;Pons, Albareda-Castellot, Sebastián-Gallés, 2012;Dufour, Brunelliere, & Nguyen, 2013;Tyler, Best, Faber & Levitt, 2014). For example, with respect to German /u-/y/, monolingual English-speaking adults continue to show the same asymmetry as English-and German-learning infants, while German-speaking adults show symmetric (and near perfect) discrimination of this contrast (Polka & Bohn, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…Broadly consistent with this idea, more recent studies have shown that linguistic experience fine-tunes this initial vowel bias to optimize access to native-language vowel categories during speech processing (Polka & Werker, 1994;Polka & Bohn, 2011;Pons, Albareda-Castellot, Sebastián-Gallés, 2012;Dufour, Brunelliere, & Nguyen, 2013;Tyler, Best, Faber & Levitt, 2014). For example, with respect to German /u-/y/, monolingual English-speaking adults continue to show the same asymmetry as English-and German-learning infants, while German-speaking adults show symmetric (and near perfect) discrimination of this contrast (Polka & Bohn, 2011). A similar pattern of developmental change emerged when Danish-speaking adults and Danish-learning infants were tested on a native contrast (i.e., Danish /e/-/ø/) and a non-native contrast (i.e., British English /ae/-/ɯ; Polka & Bohn, 2011), and when Spanish-and Catalan-learning infants were tested on discrimination of Catalan /i-e/ (Pons et al, 2012).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Asymmetries in prelexical infants' speech perception have played a major role in vowel discrimination research (see Polka & Bohn, 2011). However, the mechanisms proposed to underlie this perceptual bias (Schwartz, Abry, Boe, Menard, & Vallee, 2005) cannot easily be extrapolated to consonants, which are characterized by very different acoustic properties.…”
Section: Discussionmentioning
confidence: 99%